Bioremediation and Electricity Generation by Using Open and Closed Sediment Microbial Fuel Cells - Abbas, Syed Zaghum; Rafatullah, Mohd; Khan, Moonis Ali; Siddiqui, Masoom Raza (Frontiers in Microbiology, 2019)
The industrial contamination of marine sediments with mercury, silver, and zinc in Penang, Malaysia was studied with bio-remediation coupled with power generation using membrane less open (aerated) and closed (non-aerated) sediment microbial fuel cells (SMFCs). The prototype for this SMFC is very similar to a natural aquatic environment because it is not stimulated externally and an oxygen sparger is inserted in the cathode chamber to create the aerobic environment in the open SMFC and no oxygen supplied in the closed SMFC. The open and closed SMFCs were showed the maximum voltage generation 300.5 mV (77.75 mW/m2) and 202.7 mV (45.04 (mW/m2), respectively. The cyclic voltammetry showed the oxidation peak in open SMFCs at +1.9 μA and reduction peak at -0.3 μA but in closed SMFCs oxidation and reduction peaks were noted at +1.5 μA and -1.0 μA, respectively. The overall impedance (anode, cathode and solution) of closed SMFCs was higher than open SMFCs. The charge transfer impedance showed that the rates of substrate oxidation and reduction were very low in the closed SMFCs than open SMFCs. The Nyquist arc indicated that O2 act as electron acceptor in the open SMFCs and CO2 in the closed SMFCs. The highest remediation efficiency of toxic metals [Hg (II) ions, Zn (II) ions, and Ag (I) ions] in the open SMFCs were 95.03%, 86.69%, and 83.65% in closed SMFCs were 69.53%, 66.57%, and 65.33%, respectively, observed during 60–80 days. The scanning electron microscope and 16S rRNA analysis showed diverse exoelectrogenic community in the open SMFCs and closed SMFCs. The results demonstrated that open SMFCs could be employed for the power generation and bioremediation of pollutants.